Impact of Post-Stack Seismic Inversion on Volumetric Estimation in Pliocene Channel Reservoirs: A Case Study from the Nile Delta’s Baltim Field - EL-SAYED, Ali Saeed Ali; MABROUK, Walid M.; METWALLY, Ahmed M. (Iraqi Journal of Science, 2026)
This study addresses the challenge of identifying Pliocene reservoir channels where small quantities of hydrocarbons can cause misleading Class III AVO anomalies, leading to inaccurate predictions of commercially unviable gas. It explores whether seismic attributes, such as far amplitude, in combination with well-log data, can confirm the presence of a prospective anomaly. This is especially relevant for the Kanaria Pliocene feature within the Baltim North area, offshore in the Nile Delta. To investigate this, we employed a range of post-stack seismic inversion techniques, including colored inversion, sparse spike inversion, band-limited inversion, and model-based inversion, to delineate the hydrocarbon-rich sands in the Kanaria Pliocene sand channel. Petrophysical data from five wells (BN-3, BNE-17dir, ANDALLEB-1, TERSA-1 ST, and WB-1) were incorporated to support the analysis. Results revealed low acoustic impedance sands at both the top and base of the Kanaria Pliocene feature. The sandstones from the BN-3 and BNE-17dir wells showed significant potential, with an average shale volume of 33%, total porosity of 26%, effective porosity of 21%, and hydrocarbon saturation of 40%. Using post-stack seismic inversion, particularly color inversion (with a correlation of 0.98) and band-limited inversion (with a correlation of 0.96), the study improved the estimation of gas initially in place (GIIP). Gas in place for the Pliocene reservoirs was estimated to increase from 32.87 billion standard cubic feet (BCF) to 33.93 billion standard cubic feet (BSCF), confirming the presence of a promising anomaly and enhancing the potential for successful drilling and future development. This confirmation opens the possibility for exploration and development wells in the future.